2005
DOI: 10.1109/tgrs.2004.840646
|View full text |Cite
|
Sign up to set email alerts
|

Microwave backscatter modeling of erg surfaces in the Sahara desert

Abstract: Abstract-The Sahara desert includes large expanses of sand dunes called ergs. These dunes are formed and constantly reshaped by prevailing winds. Previous study shows that Saharan ergs exhibit significant radar backscatter ( ) modulation with azimuth angle ( ). We use measurements observed at various incidence angles and from the NASA Scatterometer (NSCAT), the SeaWinds scatterometer, the ERS scatterometer (ESCAT), and the Tropical Rainfall Measuring Mission's Precipitation Radar to model the response from san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…The strong bias can be explained by the azimuthal effects that occur due to the spatial orientation of topographic features within the sensor footprint. A similar behavior is observable also over mountainous areas and has been demonstrated in the case of scatterometer acquisitions [39,40]. Usage of only ascending or descending orbit could overcome the problem; this would, however, further reduce the temporal resolution of the product.…”
Section: Rmsd Results Analysissupporting
confidence: 66%
“…The strong bias can be explained by the azimuthal effects that occur due to the spatial orientation of topographic features within the sensor footprint. A similar behavior is observable also over mountainous areas and has been demonstrated in the case of scatterometer acquisitions [39,40]. Usage of only ascending or descending orbit could overcome the problem; this would, however, further reduce the temporal resolution of the product.…”
Section: Rmsd Results Analysissupporting
confidence: 66%
“…These differences are expected to be large over arid regions showing well-orientated structures such as sand dunes [7], [30]. The two azimuthal angles of the ASAR instrument are about 100…”
Section: A Angular Signatures 1) Azimuthal Anglementioning
confidence: 98%
“…On one hand, owing to its high temporal repetitivity (four to five days in theory) associated to a spatial resolution of about 50 km, the ERS WSC has provided useful data over the Sahel during a ten-year period [2]- [6]. Since 2001, QuickScat scatterometer observations took over from those delivered by ERS [7], although at a higher microwave frequency. Studies of these data have shown that Sahelian surfaces exhibit marked seasonal and interannual signatures [2].…”
mentioning
confidence: 99%
“…They explained this by the presence of sastrugi, which are streamlined features formed on the snow surface in the wind direction. Over land, areas of strong azimuthal anisotrophy can be found in sand deserts, where the prevailing winds form the shape and microrelief of the sand dunes (Stephen and Long 2005;Bartalis et al 2006).…”
Section: Ers Soil Moisturementioning
confidence: 99%